(untitled) (Research, Society and Development, 2022)
The referred article presents an approach regarding assistive and digital technologies in special education: what was possible in times of Covid-19 pandemic. It aims to identify which assistive and digital technologies were used by teachers in remote education for students targeting special education in two public schools in Teresina and one in Picos-PI, during the Covid-19 pandemic. For the development of the research, an exploratory field research was initially carried out, based on a qualitative approach. For data collection we used semi-structured interviews, we opted in this research, for the descriptive type, as a complement, we used the inductive method in order to better expose the object of study presented here. As possible results, we observed that the use of assistive and digital technologies does not yet occur effectively in pedagogical practices during remote teaching to students with disabilities, leaving them in a masked inclusion, that is, excluded. Thus, it is believed that the continuing education of teachers on digital and assistive technologies is necessary to favor inclusion in pedagogical practices in remote education, as well as the dialogue between teachers in the regular classroom and specialized educational services, in order to enable collaborative work that favors the effective participation of these students target audience of special education.